Assessment of surgical outcome in emergency gastrointestinal surgeries using P-POSSUM score - Hota, Prasan Kumar; Yellapragada, Harshita (International Journal of Research in Medical Sciences, 2017)
Background: The physiological and operative severity score for the enumeration of mortality and morbidity (POSSUM) and its modification, Portsmouth-POSSUM (P-POSSUM), are considered as methods of risk scoring. Application of this scoring system helps in assessing the quality of the health care provided and surgical outcome. Its utilization in our country where the level of healthcare and resources differ is limited. Hence, a prospective study to assess the outcome of emergency GI surgeries using P-POSSUM scoring system in a teaching hospital at district level was taken up. Methods: 80 cases which underwent emergency GI surgeries were studied. Using P-POSSUM equation, predicted mortality and morbidity rates were calculated and compared with the actual outcome. Statistical significance was calculated using chi square test. Results: An observed to expected ratio of 0.71 and 0.60 was obtained for mortality and morbidity respectively. No significant difference was noted between expected to observed mortality and morbidity rates with P=0.23 and P=0.09 for mortality and morbidity respectively, suggesting a reasonably good quality of outcome. P-POSSUM over predicted mortality and morbidity in low risk groups while it accurately predicted the outcome in high risk groups. Conclusions: The quality of surgical care provided and surgical outcome are comparable to other health care systems, with observed to expected mortality and morbidity ratio being nearly same. P-POSSUM can be used as a tool for outcome audits.